2004
DOI: 10.1097/00002030-200411050-00004
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 nucleoside reverse transcriptase inhibitors stavudine and zidovudine alter adipocyte functions in vitro

Abstract: The thymidine analogues stavudine and zidovudine decreased lipid content, mitochondrial activity, and adipocyte survival in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 42 publications
10
103
2
2
Order By: Relevance
“…In addition, the findings that some PIs induce mitochondrial dysfunction are novel, such alterations being generally attributed to nucleoside reverse transcriptase inhibitors (mainly thymidine analogs). 39,40 In the treatment of HIV infection, both drugs are commonly associated, which could cause major mitochondrial alterations. Whether PIs or LMNA mutations can induce direct effects on isolated mitochondria needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the findings that some PIs induce mitochondrial dysfunction are novel, such alterations being generally attributed to nucleoside reverse transcriptase inhibitors (mainly thymidine analogs). 39,40 In the treatment of HIV infection, both drugs are commonly associated, which could cause major mitochondrial alterations. Whether PIs or LMNA mutations can induce direct effects on isolated mitochondria needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was measured by means of flow cytometry and in terms of the cleavage of the death substrate PARP, as described previously. 40 The percentage of apoptotic cells with subdiploid DNA staining, located in the 'sub-G0/ G1' peak, was measured. Positive control of apoptosis was obtained by treating starved fibroblasts with staurosporine (Sigma-Aldrich) 500 nM for 20 h. Caspase-3-mediated PARP cleavage was estimated by Western blotting whole-cell lysates with an antibody (SC-7150, Santa Cruz Biotechnology) that recognizes the entire (116 000 Da) and cleaved (85 000 Da) forms of PARP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of nucleoside-induced mitochondrial dysfunction in HIV-infected patients treated with nucleosidecontaining HAART, because lipodystrophy with peripheral fat wasting is associated with a decrease in subcutaneous adipose tissue mitochondrial DNA content 62 . Disrupted pools of nucleotide precursors and inhibition of DNA pol-gamma by specific nucleoside reverse transcriptase inhibitors are mechanistically important in mitochondrial toxicity 63 .…”
Section: Mitochondrial Dysfunction and Lipodystrophymentioning
confidence: 99%
“…21 Similar findings were reported when a stavudine-based regime was replaced with a treatment containing protease inhibitors and efavirenz, an NNRTI less prone to causing mitochondrial toxicity. 22 Treatment of rat with the NRTI zidovudine causes mtDNA depletion and, moreover, several studies have indicated that anti-retroviral drugs that cause mtDNA depletion also impair adipocyte differentiation in cell culture, 7 and treatment of adipocyte cell cultures with uridine, which averts mitochondrial dysfunction, prevents NRTI-induced impairment in adipocyte differentiation 23 and ameliorates lipodystrophy 'in vivo'. 24 Therefore, extensive studies on mitochondria and HALS have demonstrated that mitochondrial disturbances in adipose tissue are capable of eliciting profound effects in adipose tissue biology and appear to promote lipoatrophy.…”
Section: Introduction: Overview Of Adipose Tissue Disturbances In Hivmentioning
confidence: 99%